The Role of e_Audit Perception: Pillars of Transparency, Accountability and Sustainability Reporting in Public Organizations - Asnawi, Meinarni; Muslimin, Ulfah Rizky; Mudassir, Annisa Fitriah (Archives of Business Research, 2025)
The development of digital technology has driven transformation in the auditing process, particularly through the implementation of e-audit. E-audit enables audit activities—such as control and risk assessment—to be conducted more automatically, systematically, and continuously. This not only accelerates the auditing process but also enhances auditors’ ability to detect potential errors, fraud, and weaknesses in internal control systems. This study aims to analyze the role of e-audit in strengthening accountability, transparency, and sustainability reporting in public organizations. It also emphasizes the importance of providing recommendations for improvement, fostering innovation and audit system development, as well as ensuring management commitment through policies, resource allocation, and the establishment of a culture of transparency. Using SmartPLS, with a sample of 67 respondents. The results indicate that e-audit perceptions do not significantly influence sustainability reporting. While accountability directly enhances sustainability report quality, transparency serves as the key pathway linking e-audit perceptions with sustainability reporting. e-audit perceptions influence transparency, which in turn mediates the relationship between e-audit perceptions and sustainability reporting. These findings highlight e-audit as a vital pillar of modern governance, reinforcing transparency, accountability, and sustainability in the public sector. Thus, e-audit can be viewed as a crucial pillar of modern governance, integrating technological efficiency with sustainability principles. Overall, these results emphasize that transparency acts as the key mediating factor linking e-audit practices to improved sustainability reporting